Unsaturated Response of Clayey Soils Stabilised with Alkaline Cements - Nuno Araújo; Manuela Corrêa-Silva; Tiago Miranda; António Topa Gomes; Fernando Castro; Tiago Teixeira; Nuno Cristelo (Molecules, 2020)
The influence of suction on the mechanical behaviour of unsaturated chemically stabilised soils is still mostly unknown and unquantified. This is also motivated by the difficulties associated with the experimental procedure required to fully characterise the unsaturated response of the soil, including its direct influence on traditional strength tests. The present paper presents the soil water retention curves obtained for a Portuguese soil before and after being stabilised with Portland cement (OPC) and an alkali-activated cement (AAC). Saturated undrained triaxial tests were also performed for the same curing conditions (0, 28, and 90 days). Previous attempts to characterise the retention curve of soils stabilised with AAC are unknown, and the results showed that the pore volume structure is already formed after 28 days, prior to the full development of the gel matrix responsible for the strength increase between 28 and 90 days. The curve changed after stabilisation, and with each binder, as the OPC presented a higher air-entry value and a narrower suction range compared to the AAC solution. The significant differences between the curves obtained from each binder suggest the future development of a methodology to assess the quality of the AAC stabilisation.